Anthropometric-Parameters and Total-Cholesterol to HDL-Cholesterol Ratio are Better in Long-Distance Cyclists (Indonesia North Coast and Tour de Borobudur 2017 Study) - Azam, Mahalul; Rahayu, Sri Ratna; Fibriana, Arulita Ika; Susanto, Hardhono; Kartasurya, Martha Irene; Bahrudin, Udin (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
Total-Cholesterol (TC) to HDL-Cholesterol (HDL-C) ratio in athletes is well-known to be better than sedentary people. However, information about comparison of TC/HDL-C in different groups of cyclists based on cycling touring characteristics and anthropometry parameters is lacking. This study aimed to compare TC/HDL-C ratio between groups based on the type of tour in cyclists population. Eighty-eight participants were recruited in this cross-sectional study. Mean differences of parameters between groups was analyzed by One-Way Anova and independent t-test, whereas multivariate analyses was conducted by binary logistic-regression. P value <0.05 was considered statistically significant. TC/HDL-C ratio in all groups were less than 4.5. There is no differences of TC-levels (NC240K: 216.6±55.04, TdB140K: 208.1±27.13, TdB100K: 203.1±31.95; p=0.427). But there is significantly different level of HDL-C (NC240K: 68.9±19.09, TdB140K: 52.1±13.9, TdB100K: 53.6±12.45; p=0.0001) and TC/HDL-C ratio (NC240K: 3.3±1.12, TdB140K: 4.2±1.07, TdB100K: 4.0±1.06; p=0.007). Between TC/HDL ratio groups (≥4 or <4), there were differences of weight, BMI, waist-circumference, hip-circumference and type of tour (p<0.05). Finally, BMI and type of tour were the most influential factor. Long-distance cyclists have a synergistic effect of lipid profile and anthropometry measurements, and heavier cycling tour participant, that represent cycling training habits, tend to have lower TC/HDL ratio(< 4).